Assessing methods and obstacles in chemical space exploration. Issue 2 (26th November 2020) - Reeves, Shawn; DiFrancesco, Benjamin; Shahani, Vijay; MacKinnon, Stephen; Windemuth, Andreas; Brereton, Andrew E.
Abstract: Benchmarking the performance of generative methods for drug design is complex and multifaceted. In this report, we propose a separation of concerns for de novo drug design, categorizing the task into three main categories: generation, discrimination and exploration . We demonstrate that changes to any of these three concerns impacts benchmark performance for drug design tasks. In this report, we present Deriver, an open‐source Python package that acts as a modular framework for molecule generation, with a focus on integrating multiple generative methods. Using Deriver, we demonstrate that changing parameters related to each of these three concerns impacts chemical space traversal significantly, and that the freedom to independently adjust each is critical to real‐world applications having conflicting priorities. We find that combining multiple generative methods can improve optimization of molecular properties and lower the chance of becoming trapped in local minima. In addition, filtering molecules for drug‐likeness (based on physicochemical properties and SMARTS pattern matching) before they are scored may hinder exploration, but can also improve the quality of the final molecules. Finally, we demonstrate that any given task has an exploration algorithm best suited to it, though in practice linear probabilistic sampling generally results in the best outcomes, when compared to Monte Carlo sampling or greedy sampling. Deriver is being made freely available, to help others interested in collaboratively improving existing methods in de novo drug design centered around inheritance of molecular structure, modularity, extensibility, and separation of concerns.